1991
DOI: 10.1056/nejm199109193251204
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Treadmill Exercise Score in Outpatients with Suspected Coronary Artery Disease

Abstract: The treadmill score is a useful and valid tool that can help clinicians determine prognosis and decide whether to refer outpatients with suspected coronary disease for cardiac catheterization. In this study, it was a better predictor of outcome than the clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
348
6
30

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 739 publications
(399 citation statements)
references
References 15 publications
15
348
6
30
Order By: Relevance
“…The Duke score was calculated as previously described. 7,8 Near peak exercise, 3 to 4 mCi of 201 Tl were injected. Patients were imaged in the supine position beginning 10 minutes after exercise.…”
Section: Exercise 201 Tl Spectmentioning
confidence: 99%
See 1 more Smart Citation
“…The Duke score was calculated as previously described. 7,8 Near peak exercise, 3 to 4 mCi of 201 Tl were injected. Patients were imaged in the supine position beginning 10 minutes after exercise.…”
Section: Exercise 201 Tl Spectmentioning
confidence: 99%
“…[3][4][5] The guidelines acknowledge that the elderly and women represent special populations in whom treadmill testing may be less accurate, but there are insufficient data to recommend stress imaging over standard treadmill testing in these groups. We recently reported that the Duke treadmill score 6,7 failed to stratify elderly patients according to risk. 8 Although single-photon emission computed tomography (SPECT) generally is more accurate for prognostic purposes than standard treadmill testing, 9 -13 there are few published data on the prognostic value of exercise myocardial perfusion imaging in the elderly, especially elderly women.…”
mentioning
confidence: 99%
“…This may seem to be a high number but in a comparable study by Mark et al [12] and in the multicentre study by Gibbons et al [8] the number of equivocals after exercise test was as high as 34Á57%. Nearly half of the patients who underwent MPS showed signs of IHD.…”
Section: Discussionmentioning
confidence: 91%
“…Symptom perception varies with activity and can be difficult to elicit. Treadmill exercise tolerance testing (ETT) can unmask symptoms; ETT findings have geometric and functional correlates in aortic regurgitation (AR) (4) and prognostic value in coronary artery disease (5) and AR (6). ET correlates with RV ejection fraction, a prognosticator in MR (7).…”
Section: Introductionmentioning
confidence: 99%